UPDATING BUILDING MAPS BASED ON OBJECT EXTRACTION AND BUILDING HEIGHT ESTIMATION - L. Zhu; H. Shimamura; K. Tachibana (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2012)
This study presents a novel approach in building change detection for map updating in urban areas. Our approach is based on the integration of building object extraction and building height estimation utilizing existing 2D building maps and newly-acquired high resolution aerial orthoimages & DSMs. In our proposed scheme, the detection of newly-built buildings is carried out based on building object extraction from orthoimages and DSMs. Detection of demolished and reconstructed buildings is performed based on estimating the height of each building using existing building maps and newly-acquired DSMs. Finally the two results are integrated together for map updating. The experimental results showed that the proposed technique performed satisfactorily well in detecting newly-built buildings, demolished buildings and reconstructed buildings, and was very effective in reducing the problem of misdetection and false detection. This technique is already integrated into a practical system for building maps updating.